TI_GERICHTE 12.2015.69 vom 16. Februar 2016 , Riconoscimento ed exequatur di sentenza straniera - appello nello stato d'origine - TI Tribunale d'appello (2016)
Riconoscimento ed exequatur di sentenza straniera - appello nello stato d'origine